2008
DOI: 10.1063/1.2901161
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in crystallization time of Sb:Te films through addition of Bi

Abstract: The electrical, optical, and phase change properties of bismuth doped Sb 8 Te 2 films have been characterized. Thin films of the material, with up to 15 at. % percent Bi, have been synthesized; amorphous films were stable at room temperature with a Bi concentration of up to 13 at. %. The effect of Bi on the phase change properties of the film is shown to reduce the crystallization time by an order of magnitude while the crystallization activation energy reduction is minimal; 0.2 eV. Over the last 30 years, 1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Wang and co‐workers found that doping GST with 3.3 at% Bi improved the crystallization speed and lowered the crystallization temperature, which was correlated with a reduction in the crystallization activation energy. Simpson et al likewise found that Bi doping decreased the crystallization time in Sb 2 Te 8 , although it was noted that, in contrast to the work found elsewhere, the doping appeared to have little effect on the activation energy. It was speculated that the faster crystallization may be due to an increase in free volume in the amorphous material, and a corresponding decrease in viscosity, facilitating easier atomic diffusion during crystallization .…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Wang and co‐workers found that doping GST with 3.3 at% Bi improved the crystallization speed and lowered the crystallization temperature, which was correlated with a reduction in the crystallization activation energy. Simpson et al likewise found that Bi doping decreased the crystallization time in Sb 2 Te 8 , although it was noted that, in contrast to the work found elsewhere, the doping appeared to have little effect on the activation energy. It was speculated that the faster crystallization may be due to an increase in free volume in the amorphous material, and a corresponding decrease in viscosity, facilitating easier atomic diffusion during crystallization .…”
Section: Introductionmentioning
confidence: 87%
“…In spite of these caveats, the present simulations do seem to reproduce the trend in experimental growth‐rate enhancement imparted by Bi doping. To investigate the mechanism proposed by Simpson et al, we studied the effect of the dopant on the compressibility of the amorphous and crystalline models. To do this, the volume of each model was changed by ±500 Å 3 (corresponding to volume reductions and expansions of up to ≈10%) in eleven equal steps, with the atomic positions being scaled accordingly, and the total energy was obtained after ionic relaxation.…”
Section: Crystallization Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also shown that Bi doping into Sb 80 Te 20 can further reduce crystallization time but lead to a low crystallization temperature or poor archival stability [4]. In contrast, by adding Ge, Ag, In, and Ga into Sb 70 Te 30 or Sb 80 Te 20 , a good archival stability is achieved, but the crystallization rate slows [1,2,5].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to conventional static testers, 6 the system monitors the transmission of light through the sample with nanosecond time resolution. To ensure that the probe beam measures the center of the pump beam's spot both laser beams were coupled into a single mode optical fiber.…”
mentioning
confidence: 99%